TOLERANCE OF WOMEN IN ISLAM - Ortikova Dilbar Ortikovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article scientifically analyzes the leading role of tolerance towards women in Islam. In the Ancient East, women played an invaluable role in the development of spirituality and enlightenment. Turning over the pages of history, testifying to the ancient labyrinth, we see that the names of people and heroes are glorified in all spheres of our society. It is scientifically studied that the greatest scientists of mankind have always tried their best to make women’s labor easier and improve their living conditions, while great poets and writers have portrayed women in elegant works.